Effect of Inhalation Steroids in Children with Coexistent Atopic Disorders & Nephrotic Syndrome on Prevention of Relapses of Nephrotic Syndrome - Mauskar, Anupama; Mandhani, Geeta; Deore, Pawan (Indian Journal of Case Reports, 2015)
In many nephrotic syndrome children, it has been observed that onset of rhinitis and/or wheezing attacks precipitate the relapse of nephrotic syndrome. This association is known since long time. We decided to observe the response of inhalation steroids in prevention of relapses of nephrotic syndrome in children who presented with frequently relapsing nephrotic syndrome and coexistent atopic disorders.